Update on Pediatric Hip Imaging - Herregods, Nele; Vanhoenacker, Filip M.; Jaremko, Jacob L.; Jans, Lennart (Seminars in Musculoskeletal Radiology, 2017)
Hip disorders are common in children. Prompt diagnosis and treatment are important because of the potential complications. Symptoms are frequently nonspecific, and clinical examination can be difficult and unreliable, especially in smaller children. Therefore, imaging can be valuable. Radiography and ultrasound remain the initial imaging modalities of choice. Increasingly, magnetic resonance imaging is obtained for assessing the pediatric hip, although the long imaging time and need for sedation may limit its use in daily practice. Because of the exposure to ionizing radiation, the use of computed tomography and bone scintigraphy in children is limited to selected cases. Pediatric hip pathology varies depending on patient age. This article provides an overview of common hip pathologies in children including congenital and developmental pathologies, trauma, infectious processes, inflammatory disease, and neoplasm. The age of the child, history, and clinical examination are essential to narrow down the differential diagnosis and subsequent selection of the appropriate imaging modality.
Keywords: hip; pediatric; imaging